Intent-based UAV swarm network: management architecture, key technologies, and future vision - LI Xuan; LI Haiyan; ZHANG Lu; ZHANG Yuhang; ZHANG Haojie (Dianxin kexue)
As an integral part to the air, space and ground integrated network, unmanned aerial vehicle (UAV) swarms have shown broad application prospects in complex tasks such as emergency search and rescue, offensive and defensive confrontation, intelligence reconnaissance and surveillance. The advancements in unmanned technology, coupled with the increasingly rich applications of multi-UAV collaborative intelligence, have engendered new requisites for the information exchange capabilities within UAV swarm networks. Under the umbrella of intent-based network architecture, UAV swarms are capable of autonomously managing the network, thereby mitigating the intricacies inherent in network management. Introducing intent-driven network into UAV swarm systems urgently requires breakthroughs in smart autonomous network technology to enhance the adaptability of intelligent groups in high-dynamic and uncertain environments. A new perspective and method for the collaborative operation and intelligent decision-making of UAV swarms was provided. The architecture, key technologies, and prospects of intent-based UAV swarm networks management were reviewed. Through in-depth analysis and discussion, a solid theoretical foundation and technical reference were aimed to be provided for the future development of UAV swarms.